Effect of Geophila macropoda (Rubiaceae) as “weed cover” on hydric erosion in banana plantations, Guápiles , Limón , Costa Rica. (UNED Research Journal, 2016)
The establishment of banana companies in Costa Rica brought employment and infrastructure improvements, but also social problems, destruction of forests, soil erosion and pollution of rivers and streams. Erosion in banana plantations may be diminished with plant cover. Here we analyze the effect of the plant Geophila macropoda on erosion caused by water in Guápiles, Costa Rica. We chose three soil classes I, II and III with and without G. macropoda. Between June and August 2012 periodic measurements were performed once a week, covering periods of low, medium and high rainfall. We found that erosion increases with precipitation and that cover with this plant reduces erosion in all soil types.
Keywords: runoff; erosion; weeds; crop; rain; sediments